Empowering Village Women Through Home Industry Batik Prima Jaya to Create Local Economic - Kembaren, Mardiah Mawar; Irsad; Lubis, M. Husnan; Yudhistira, Eko; Gunaika, Raka (Talenta Publisher, 2024)
Efforts to empower women are part of human development as a resource that has considerable potential and can be developed in the context of national development. There is a phenomenon regarding women in low economic conditions, where the patriarchal cultural system has indirectly placed restrictions on women so that inequality (gender) arises, which has also given rise to the closeness of women's identity to poverty. Therefore, to equalize this position, an activity to empower village women through the Primajaya batik home industry is needed in order to increase local economic independence. The aim of this community service is to shape individuals and communities to become independent. This independence includes economic independence, independence in thinking, acting and relying on what they do. Community empowerment aims to make people independent, have the potential to be able to solve the problems they face, and be able to fulfill their needs without depending on outside parties for their lives.